2018
DOI: 10.1002/mmce.21524
|View full text |Cite
|
Sign up to set email alerts
|

A novel wideband Minkowski fractal antenna with assistance of triangular dielectric resonator elements

Abstract: This article concentrates on the design and analysis of a novel Minkowski fractal‐based antenna design with the aid of triangular dielectric resonator (TDR) elements for wideband wireless applications. TM101z mode is excited inside equilateral TDR antenna with the help of coaxial probe feed. Wide impedance bandwidth has been achieved by reducing the quality factor with the help of increasing surface area‐to‐volume ratio of radiating structure. Another important feature of this article is that recurrence formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The triangular shaped dielectric resonator antennas (DRAs) of various forms are reported in the literature, 1‐19 among which, the equilateral triangular dielectric resonator antennas (ETDRAs) are quite popular.…”
Section: Introductionmentioning
confidence: 99%
“…The triangular shaped dielectric resonator antennas (DRAs) of various forms are reported in the literature, 1‐19 among which, the equilateral triangular dielectric resonator antennas (ETDRAs) are quite popular.…”
Section: Introductionmentioning
confidence: 99%
“…However, our proposed rhombic DRA is geometrically different, providing a percentage impedance bandwidth of 31.64%. Table shows the comparison of the proposed rhombic DRA with a recently reported wideband design using equilateral triangular DRA . The percentage bandwidths are almost comparable, however, the new rhombic DRA achieved a better gain in the overlapping operational bandwidth when compared with the wideband equilateral triangular DRA.…”
Section: Design Of Wideband Rhombic Dramentioning
confidence: 88%
“…13, it can be observed that the impedance bandwidth is increasing after each condition. The reason for bandwidth enhancement is due to a decrease in the volume to the surface area of the antenna structure [13]. The calculated ratio of volume to the surface area in zeroth iteration, first iteration with single CDRA, first iteration with dual CDRA, second iteration with single CDRA, second iteration with dual CDRA, third iteration with single CDRA, and third iteration with dual CDRA is found to be 4.34, 4.12, 3.97, 3.78, 3.55, 3.23, and 3.11, respectively.…”
Section: Physical Aspect Of Proposed Antenna Geometrymentioning
confidence: 99%
“…Spidron and Pixelated is also important fractal geometry for designing of wideband DRA [11, 12]. Sur with her research group [13] proposed Minkowski fractal geometry, with the help of triangular DRA, which offers ∼32.64% fractional bandwidth.…”
Section: Introductionmentioning
confidence: 99%